2006
DOI: 10.1002/fuce.200500090
|View full text |Cite
|
Sign up to set email alerts
|

Ageing Mechanisms of Proton Exchange Membrane Used in Fuel Cell Applications

Abstract: Degradation processes of both sulfonated polyimide (sPI) and sulfonated polyetheretherketone (sPEEK) membranes were studied in‐situ in fuel cells. Ex‐situ ageing protocols were developed for both polymers and model compounds. On the one hand sulfonated polyimides are shown to be mainly sensitive to hydrolysis though an additional thermo activated oxidation process occurs in fuel cell conditions and at least accelerates the degradation. On the other hand sulfonated polyetheretherketone are insensitive to hydrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…The dominant degradation pathway is the addition of HOc to the aromatic ring, usually ortho to the alkyl-or RO-substituent. Studying the degradation of sulfonated aryletherketone in H 2 O 2 , Perrot et al 127 found that ether linkages are much more sensitive to oxidation than ketone linkages. Their degradation leads to polymer chain scission and the formation of both carboxylic and phenol end chains.…”
Section: Durabilitymentioning
confidence: 99%
“…The dominant degradation pathway is the addition of HOc to the aromatic ring, usually ortho to the alkyl-or RO-substituent. Studying the degradation of sulfonated aryletherketone in H 2 O 2 , Perrot et al 127 found that ether linkages are much more sensitive to oxidation than ketone linkages. Their degradation leads to polymer chain scission and the formation of both carboxylic and phenol end chains.…”
Section: Durabilitymentioning
confidence: 99%
“…Elemental analysis for C 13 121.8 (C h ); 121.2 (C h' ); 118.4 (C g ); 111.0 (C g' ); 101.6 (C c ); 101.4 (C a ).…”
Section: Dabimentioning
confidence: 99%
“…These qualities motivated the choice of polyimides as the polymer backbone of the polymers synthesised in this work. A disadvantage of polyimides is their low resistance to hydrolysis in acidic medium [13], [14]. To overcome this drawback we have chosen dianhydride monomer with the highest hydrolitical stability reported so far [15], [16] Moreover, the synthesis of copolymers might be a promising strategy to join a combination of properties in a single material [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, they suffer from rather low water stability, which limits their further development for practical applications. [9][10][11] To improve the PEM performance and especially the water stability of SPIs, novel sulfonated diamines have been developed, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] among which 4,4 0 -bis(4-aminophenoxy)biphenyl-3,3 0 -disulfonic acid (pBAPBDS) and 2,2 0 -or 3,3 0 -bis(3-sulfopropoxy)benzidine (2,2 0 -or 3,3 0 -BSPB) are typical ones. SPIs based on these sulfonated diamines show higher water stability and better fuel-cell performance comparable to that of Nafion 117.…”
Section: Introductionmentioning
confidence: 99%